Studi Komparasi Peran Manajerial Kepala Madrasah terhadap Kepuasan Kerja Guru dan Reputasi Madrasah di Kabupaten Sidoarjo - Soraya, Irma (Jurnal Aplikasi Manajemen, 2014)
The study is aimed at investigating 1) The order of managerial roles performed by the madrasah's principals in doing the managerial process at the madrasahs in the district of Sidoarjo. 2) The influence between the difference of role and the job satisfaction of the teachers at those madrasahs. 3) The influence of the difference in role towards the reputation of madrasahs among the society in the district of Sidoarjo. The result of the study illustrates that the managerial role in madrasahs are: 1) as figure, 2) as leader, 3) as allocator of resources, 4) as problem solver, 5) as speaker, 6) as entrepreneur, 7) as information disseminator, 8) as negotiator, 9) as communicator/link, and 10) as monitor. From the test it was found thatÂ  there is difference in roles played by the principals yet it does not affect the job satisfaction of the teachers and not the reputation of madrasahs among the society as well. Based on the result of the study the researcher suggests that those roles are depicted in more practical and doable forms. Secondly, it is important to advance the madrasahs principals'competence in decisional and informational skills. This is important to help the principals progress quickly.